Automated assistance in the formulation of search statements for bibliographic databases - Oakes, Michael P; Taylor, Malcolm J (Information processing & management, 1998)
We report on the design and construction of features of an automated query system which will assist pharmacologists who are not information specialists to access the Derwent Drug File (DDF) pharmacological database. Our approach was to first elucidate those search skills of the search intermediary which might prove tractable to automation. Modules were then produced which assist in the three important subtasks of search statement generation, namely vocabulary selection, the choice of context indicators and query reformulation. Vocabulary selection is facilitated by approximate string matching, morphological analysis, browsing and menu searching. The context of the study, such as treatment or metabolism, is determined using a system of advisory menus. The task of query reformulation is performed using user feedback on retrieved documents, thesaurus relations between document index terms and term postings data. Use is made of diverse information sources, including electronic forms of printed search aids, a thesaurus and a medical dictionary. The system will be of use both to semicasual users and experienced intermediaries. Many of the ideas developed should prove transportable to domains other than pharmacology: the techniques for thesaurus manipulation are designed for use with any hierarchical thesaurus.